Average Harvesting Charges for Florida Citrus, 2002-2003 - Ronald P. Muraro (EDIS, 2004)
A survey was conducted in Spring of 2003 to collect Florida citrus harvesting charges (picking, roadsiding, and hauling). Harvesting charges for the 2002-2003 season were collected for both fresh and processed market citrus fruit. The survey was not a statistically chosen sample; therefore, the charges may not represent Florida's total citrus industry. The participants were chosen because of their willingness to provide their harvesting charges. The survey will continue as long as there is adequate participation. This is EDIS document FE435, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published October 2004.